Investigation of the Candelstick [sic] Park wind problem. Vol. 2, Wind-tunnel model study - Cermak, J. E. (Jack E.), author; Malhotra, Ramesh Chandar, author; Plate, Erich J., author; Colorado State University, College of Engineering, Fluid Mechanics Program, publisher (Colorado State University. Libraries, 1963)
The overall purpose of this investigation is to determine whether or not there are practical methods for controlling the afternoon winds at Candlestick Park in order to alleviate the unsatisfactory wind conditions which now exist. Field observations have shown that two characteristic and distinctive wind flow patterns exist within the stadium. Each results from the interaction of Bay View Hill on the unidirectional air flow approaching the stadium complex. These wind conditions have been reproduced in a 1:768 scale model of the Bay View Hill-stadium complex, demonstrating that the wind-flow patterns observed in the model are directly correlated with those in the stadium complex, i.e. the prototype. Accordingly, changes in the wind-flow patterns resulting from modifications in the model can be evaluated in terms of corresponding modifications in the prototype. Approximately 150 different model-wind flow situations have been examined. From the results obtained it is evident that elimination of the objectionable features of the existing flow patterns, and a general reduction in wind speed within the stadium, can be achieved if both Bay View Hill and the stadium are modified as follows: Bay View Hill - Cut a slot through the south end of the hill tangent to the Left-Field edge of the stands or, remove the southerly portion of the hill. Stadium - Partially cover the stadium with a protective dome extending beyond the infield, or erect a vertical screen on top of the rim between 50 and 100 feet high, or install vanes on top of the rim to deflect the wind vertically. Modifications which are not effective singly or in combination includes: Complete removal or reduction in elevation of Bay View Hill; partial or complete extension of the upper stands around the outfield; addition of solid, porous or deflecting barriers on Bay View Hill or across left field or completely around the outfield.
Wind-tunnel model study
Investigation of the Candlestick Park wind problem. Vol. 2, Wind-tunnel model study
CER63JEC-RCM-EJP27.
July 1963.
Under contract with Metronics Associates, Inc.
Keywords: Stadiums -- California -- San Francisco -- Aerodynamics; Winds -- California -- San Francisco; Wind resistant design -- California -- San Francisco; Wind tunnel models; Buildings -- Aerodynamics